Particularities of explosive strength training in the special stage of youth taekwondo players (RIAF. International Journal of Physical Activity, 2023)
Explosive strength training is currently considered an essential element in the planning of training in the sport of Taekwondo, aiming to achieve acceleration in strikes with jumps, spins, and consequently, the movements of the taekwondo practitioner. The combination of methods for explosive strength training has been described as an effective strategy based on the variants of this manifestation. The research focused on the youth category team from the province of Holguín. Concepts, research, evaluations, and the coach's actions were taken into account, as well as the methodological requirements for developing this ability through weightlifting exercises and planned jumps during the special preparation phase according to the power zone. This paper presents a theoretical review of the main systems applied to the methodology of explosive strength training during the special preparation phase in Taekwondo.
Keywords: Taekwondo; Explosive force; Special stage; Youth